New Cave Arrhopalitidae (Collembola: Symphypleona) from the Crimea (Ukraine) - Vargovitsh, Robert S. (Zootaxa, 2009)
Caecus and pygmaeus groups of species of the genus Arrhopalites Börner, 1906 are discussed and redefined. Separate generic status for pygmaeus-group sensu lato under the name Pygmarrhopalites is proposed. Five new species and one new subspecies of family Arrhopalitidae from 38 caves of 4 karstic massifs of the Crimean Peninsula are described, illustrated and compared with similar species: Arrhopalites karabiensis, A. peculiaris, Pygmarrhopalites tauricus, P. kaprusi, P. pseudoprincipalis and P. principalis skelicus. A key to the species of the family occurring in Crimean caves is given.